Government responses to online disinformation unpacked - Samuel Cipers; Trisha Meyer; Jonas Lefevere (Internet Policy Review, 2023)
This article collects, categorises and analyses responses (n=239) to online disinformation from 103 countries, ten international and regional organisations across six continents (through 2021). We categorised each initiative into eleven non-mutually exclusive categories according to intent, objective and type of disinformation targeted. We also set up a comparative research design to assess whether different types of governments (democratic/authoritarian) approach the fight against online disinformation differently, whether the amount of press freedom in a country has a significant correlation with the response types, and whether the overall wealth of a nation (measured in GDP per capita) impact the (diversity of) responses. The results show an evolution of the focus of government responses to online disinformation over time. Most crucially, we find that democracies, with high levels of press freedom, have a more holistic approach to countering online disinformation, focusing comparatively more on the integrity of their election process, media and education initiatives, and that countries with a higher GDP have more initiatives and legislation in place than countries with a lower GDP. Authoritarian countries generally formulate broad legislation that is also often incorporated into their penal code.
Keywords: 300; Disinformation; Freedom of expression; GDP; Public policy; covid-19